1989
DOI: 10.1128/cmr.2.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory aspects of filariasis

Abstract: Human filarial infections afflict over 150 million persons worldwide and are major causes of morbidity in many developing countries. Onchocerca volvulus infection is a leading preventable cause of blindness, while bancroftian and brugian filariasis may produce lymphatic obstruction of the genitalia and extremities (elephantiasis). Definitive diagnosis of these helminthic infections currently depends on demonstration of microfilariae in host tissues, i.e., the skin in the case of O. volvulus and the bloodstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 116 publications
0
37
0
Order By: Relevance
“…There are eight species of filariae that usually infect humans, and of these, four (Wuchereria bancrofti, Brugia malayi, Onchocerca volvulus, and Loa loa) cause the most severe infections (268).…”
Section: Infections Caused By Filariaementioning
confidence: 99%
“…There are eight species of filariae that usually infect humans, and of these, four (Wuchereria bancrofti, Brugia malayi, Onchocerca volvulus, and Loa loa) cause the most severe infections (268).…”
Section: Infections Caused By Filariaementioning
confidence: 99%
“…Chyluria and other chronic manifestations of filariasis, including lymphoedema and hydrocele, may occur many years after the death of the adult worm. 4,16 Furthermore, reliable detection of microfilariae in a thick blood film Chyluria and advanced carcinoma of the prostate SA Cluskey et al from an infected individual may depend on the time of day that the specimen was obtained. 16 Ultrasound scanning is utilised in some endemic regions to identify adult worms in the lymphatic vessels around the spermatic cord.…”
Section: Discussionmentioning
confidence: 99%
“…4,16 Furthermore, reliable detection of microfilariae in a thick blood film Chyluria and advanced carcinoma of the prostate SA Cluskey et al from an infected individual may depend on the time of day that the specimen was obtained. 16 Ultrasound scanning is utilised in some endemic regions to identify adult worms in the lymphatic vessels around the spermatic cord. 17 Detection of antibodies against the adult worm is considered to be a reliable test for infection, 18 although this was not available to us.…”
Section: Discussionmentioning
confidence: 99%
“…44-14 kDa of B. malayi (Cheirmaraj and Harinath, 1991), 25 kDa (Kazura et al, 1986), 92-25 kDa (Parab et al, 1990) of Mf were earlier found to be immunoreactive using human bancroftian sera. Molecular weight < 200,[40][41][42][43][44][30][31][32][33][34][35][36][23][24][25][26][27][28][20][21][22] kDa of B. malayi adult induced protection against L 3 in Balb/c mice Hayashi et al, 1989), 97 kDa of B. malayi Mf and adults induced partial stage specific protection against B. malayi Mf in mice (Nanduri and Kazura, 1989).…”
Section: Introductionmentioning
confidence: 99%